Ideological Meanings in The Guardian’s Reporting of Nicolás Maduro’s Capture - Suswanto Ismadi Megah; Sri Sugiharti; Zulida Abdul Kadir; Satria Agust; Saira Kazmi (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2026)
Media discourse plays an important role in constructing and disseminating ideological meanings, particularly in political reporting, where language is used to represent social actors and political events from specific perspectives. This study investigates the ideological stance underlying news reports on the United States government's and politicians' reactions to the capture of Nicolás Maduro, as reported in The Guardian Online Newspaper. The study employs Martin and White's (2005) Appraisal Theory, focusing on the Attitude subsystem, in conjunction with Fairclough's (1995) Critical Discourse Analysis (CDA) framework. The data consist of three news reports published by The Guardian on January 3 and 4, 2026, totaling 1,567 words. The analysis examines how evaluative language is utilized to construct particular representations of social actors and political actions. The findings reveal that The Guardian predominantly employs negative evaluative polarity and frequently expresses attitudes through indirect invocation, in which evaluative meanings are implied and subsequently reinforced through quoted statements. The United States government and politicians are primarily positioned as the appraisers and active social actors, whereas Nicolás Maduro is predominantly represented as the appraised social actor. The study further demonstrates that the news reports construct the capture of Maduro as a protective and legitimate action associated with concerns over security and anti-drug enforcement. Through these evaluative patterns, the newspaper reflects and reproduces particular ideological perspectives regarding the political event. The findings contribute to a deeper understanding of how media discourse utilizes evaluative language to shape ideological representations in contemporary political reporting.